Design of a Computerized Fence at Nyabikoni Campus Kabale University. - Kawesa, Eden (Kabale University, 2023)
This report is about a design of a perimeter fence for Kabale University Nyabikoni Campus. This report contains four chapters, Chapter 1 is the introduction of the proposal that states the contents of the background of the project, how the problem was identified and why the project viable, Chapter 2 contains the literature review, works and related information by other scholars about design mainly architectural working drawings, Chapter 3 outlines the methodology of how the project was done; these are sequential methods for the process, Chapter 4 discusses the results and project discussions that involve details of the budget, work plan, appendices and reference.